INTERNATIONAL AND NATIONAL EDUCATIONAL EXPERIENCES ON STRATEGIES FOR PROMOTING STUDENTS' MENTAL HEALTH AND DEVELOPING CRITICAL THINKING IN THE MODERN EDUCATIONAL SYSTEM. (Universal International Scientific Journal, 2026)
This thesis provides a detailed overview of foreign experiences in critical thinking. It provides explanations on the practical application of these methods. In addition, it provides recommendations on methods and technologies that can be used in education.
Keywords: Critical thinking, intellectual ability, individual approach, thinking, Bloom, problem analysis.